Pembatasan Masa Jabatan Presiden dalam Rangka Mewujudkan Negara Hukum Demokratis - Gusman, Delfina Gusman; Syofyan, Yunita Syofyan (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum, 2023)
Indonesia as rule of law by characteristic republic and presidential system. Article of 1 paragraft 2 regulation of 1945 so “sovereignty in the handful of society and implementation according of regulation of 1945